Las “ciudades digitales”: un nuevo reto para las Administraciones Públicas españolas - Abuín Vences, Natalia (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2008)
Technology´s spectacular advance and the Internet development between the Spanish citizens, allows us to speak about an absolutely digitized society. In this article we make a revision about “digital city” concept, and about the legislation, the processes, the problems and the necessary technology for its development in our country.